Structural evolution of carbide-derived carbons upon vacuum annealing - Osswald, Sebastian; Chmiola, John; Gogotsi, Yury (Carbon (New York), 2012)
Microstructure and surface moieties of porous carbons play a significant role in affecting their performance in a variety of applications. While it is well known that high-temperature treatments of porous carbons can influence the microstructure, no systematic studies have been done on carbide-derived carbons. We show that vacuum annealing increases the pore volume and specific surface area of titanium carbide-derived carbon with no significant change in the pore size up to 1500°C. This treatment produces porous carbons with subnanometer porosity and a specific surface area up to 2000m2/g, while treating the samples at temperatures above 1600°C increases the pore size above 1nm because of graphitization and collapse of the micropore structure. The results demonstrate that vacuum treatment can be used to further tune the pore structure and potentially the surface functionality of carbide-derived carbons for supercapacitor electrodes, gas chromatography, sorption, sensing and other applications. Vacuum annealing of carbide-derived carbon is therefore a suitable alternative to conventional microstructure modification methods, such as gas or liquid phase activation, which are subject to substantial sample loss and result in additional surface functionalization.